PRINCIPLES OF LEGAL COMMUNICATION: THEORETICAL AND LEGAL ASPECTS - Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: the article deals with the theoretical and legal aspects of the principles of legal communication. The views of scientists on the problem of the principles of law are analyzed. Methods of research: philosophical-ideological, general scientific and special methods were used in the work. Results: the principles of legal communication are defined. It is concluded that the principles of legal communication are the basis for the formation of legal values of the modern information and legal society. Discussion: the search for ways of effective legal communication in the context of the formation of information and legal society.